Interdisciplinary cooperation in the integrated information learning environment of technical university - S. Yu. Rzheutskaya; M. V. Kharina (Открытое образование (Москва))
The objective of the article is to analyze the integrated learning environment facilities in order to organize interdisciplinary cooperation within the learning process at the technical university. The problem of interdisciplinary cooperation is the key one for university teachers when putting the competence approach into practice, for according to the state educational standards, cultural and professional competences are integrative and must be developed in the process of studying of various subjects. The one more goal to be achieved only by means of realizing interdisciplinary cooperation is the development of professionally important personal qualities among the future engineers. The integrated learning environment that is the object of the research work has already been formed at the Vologda State University and used in the learning process of the bachelors and masters in several fields of studying connected with IT. The foundation of this learning environment is laid by the system of distance learning MOODLE, supplemented by program components of own authoring. Such components are integrated with MOODLE by means of common database gathering the whole information about the learning process. Among software of own authoring we can point out the interdisciplinary distance training system, embracing such disciplines as programming, database technologies and other related sciences, and including automatic checking of students’ solutions and trainer for individual progress in English language. During the researching process we devised the structure-functional model of interdisciplinary cooperation with the use of the integrated learning environment, presenting available forms of cooperation of the learning process individuals at the interdisciplinary level and the means of realizing this cooperation. By now all the structural and functional components of the model have been embedded in the learning process and proved to be viable. The article presents the authors’ experiments on the organization of various forms of interdisciplinary cooperation in compliance with this model by the example of the development of foreign communicative competence among the future engineers closely connected with their core disciplines. The results of these experiments showed the students’ progress in language proficiency when the interdisciplinary forms of studying are used. In the whole the results of the research show that modern IT capabilities enable us to overcome narrow disciplinary approach to the learning process at the technical university and rise the level of interdisciplinary cooperation. Of course, interdisciplinary cooperation is only one aspect of the perspective use of the integrated information learning environment, its capabilities are much greater, some of them are already used in practice, and many have yet to explore and implement. The environment itself is in permanent development, in this regard, new opportunities appear, allowing to raise quality of education of students in a technical university.